Dynamic Analysis of a 4–Axles Railway Vehicle Model - Zuzana Ondrova (Communications - Scientific letters of the University of Zilina, 2009)
The paper deals with using dynamic simulations in fields of construction, production and operating of railway vehicles. It contained process of dynamics solution of choices referent vehicle by the help special solution software – MSC ADAMS. The creating of virtually model included creating model for railway vehicle and the model of track which is assigned for motion of railway vehicle.In the end of paper there are summary of obtained data from dynamic analysis which give us integrated view of railway vehicle behavior by the run on given track.